Cost of COVID-19 Mass Vaccination at Ngampilan Health Center Yogyakarta - Marlita Putri Ekasari; Ragil Setia Dianingati; Lili Nur Indah Sari (Indonesian Journal of Pharmacy, 2025)
The Corona Virus Disease-19 (COVID-19) outbreak had a significant impact on every sector. To minimize the case and the mortality rate, the vaccination program is accelerated using every possible strategy. One of the strategies employed in Indonesia is the mass vaccination program. This study aimed to estimate the unit cost of the mass vaccination program service delivery of COVID-19 Sinovac vaccine per dose and per fully vaccinated (2-dose) against COVID-19 in a public health center facility in Yogyakarta city. The costing study used activity-based cost according to the financial data, interviews, and direct observations. The incremental financial cost and full economic cost were calculated using the government or provider's point of view. The total cost is then divided by the number of doses injected and multiplied by two to get the cost per fully vaccinated person. The incremental financial cost and economic values per dose were USD32.64 and USD33.57, while for the fully vaccinated person (2-dose) using Sinovac Vaccine were USD 65.28 and USD 67.15, respectively. Based on the one-way sensitivity analysis, the unit cost per fully vaccinated is influenced by vaccine price and the number of vaccinated people per mass vaccination session.